Laser Micromachining of Glass, Silicon, and Ceramics - L. Rihakova; H. Chmelickova (Advances in Materials Science and Engineering)
A brief review is focused on laser micromachining of materials. Micromachining of materials is highly widespread method used in many industries, including semiconductors, electronic, medical, and automotive industries, communication, and aerospace. This method is a promising tool for material processing with micron and submicron resolution. In this paper micromachining of glass, silicon, and ceramics is considered. Interaction of these materials with laser radiation and recent research held on laser material treatment is provided.